THE INFLUENCE OF CONSUMER LIFESTYLE IN THE REPUBLIC OF SERBIA ON CONSUMER ETHNOCENTRISM - Gašević, Dragana Lj; Vranješ, Marija D; Tomašević, Dragana D (International Journal of Economic Practice and Policy, 2020)
Consumer behavior is determined by a number of factors. One of them is ethnocentric tendencies. Ethnocentric consumers are those who prefer to buy domestic products rather than products of foreign origin. As not all consumers are equally ethnocentric, the main objective of the paper is to identify the individual and cumulative impact of certain components of respondents’ lifestyle on consumer ethnocentrism. The results have shown a statistically significant influence of three dimensions of lifestyle (personality traits, practical and rational purchasing behavior and fashion awareness) on consumer ethnocentrism of respondents in the Republic of Serbia. The analysis of the gathered data was performed using factor analysis and regression analysis. The research results have provided a great deal of meaningful information necessary for strategic management and decision making. In addition, the base for devising better quality strategies for approaching individual groups of consumers is provided, all depending on the degree of their consumer ethnocentrism.